School refusal : clinical characteristics, treatment and outcome - Engelbrecht, Leon Anton (Division of Child and Adolescent Psychiatry, 2017)
Clinical characteristics, methods of treatment and outcome in School Refusal have been investigated. School refusal/phobia has been reported in the literature not to be a true clinical entity with a uniform aetiology, psychopathology, course, prognosis and treatment, but rather a collection of symptoms or a syndrome occurring against the background of a variety of psychiatric disorders. Aetiological and precipitating factors also vary with age, psychosocial level of development and personality factors in the individual child, family structure and function, and the school setting. Data were collected retrospectively from 20 cases treated at the Child and Family Unit, Red Cross War Memorial Children's Hospital, Cape Town during a specific time period. Analysis of the data revealed a gender distribution of 11 boys and 9 girls; 1 girl, 5 - 8 years old and 11 boys and 8 girls 9 - 13 years old. One Asian, no Black, 13 Coloured and 6 White children were represented. A large section of the sample population represented the lower socio-economic group as determined by parental qualification and occupation. Most of the families tended to consist of more than 2 children (5 member families). Family dysfunction was recorded in all but one case, with evidence of a recognizable psychiatric disorder also recorded quite frequently in the nuclear family members. Educational difficulties were recorded in a third of the sample together with below average total IQ scores in virtually all the subjects evaluated. The bulk of referrals were from medical practitioners and relatively few from schools. Refusal to attend school was of relatively short duration in three-quarters of the sample. Most of the cases were first time school refusers. Accompanying symptoms or problems were mainly anxiety or depression - related whereas significant associated events were mainly family - oriented. Psychiatric disorders diagnosed most often were anxiety and affective disorders with overlap of the 2 conditions recorded in half the sample. Response to treatment was positive in two thirds of the sample and a combination of treatment methods proved to be the most successful treatment plan. School refusal as investigated in this study, was well represented in a population of children treated at a Child Psychiatric Out-Patient Unit. A high rate of resemblance on various aspects of school refusal was recorded between the study sample and reports in the literature reviewed.